Method and technology for monitoring and forecasting the atmospheric air condition by means of universal information-measuring system with the applicatin of mobile devices - Mokin, Vitalii; Dziuniak, Dmytro; Bondaletov, Konstiantyn; Oleynik, Valentina (Scientific Works of Vinnytsia National Technical University, 2016)
The paper considers urgent problem of monitoring and prediction of the atmospheric air condition in the city, where the main factor of pollution is motor vehicle emissions on the highways. The developed new method and technology for solving this problem are based on the application of a universal information-measuring system, built on the basis of mobile devices for monitoring and controlling the atmospheric air condition and the sources of its pollution. An experiment to test this technology, conducted in the streets of Vinnytsia, has confirmed its efficiency.